Controlling the electrochromic properties of conductive polymers using UV-light. Issue 17 (5th March 2018) - Brooke, Robert; Edberg, Jesper; Iandolo, Donata; Berggren, Magnus; Crispin, Xavier; Engquist, Isak
Abstract : A new technique for patterning and tuning of electrochromic properties of conductive polymers was used to make dual image displays. Abstract : The phenomenon of electrochromism in conductive polymers is well known and has been exploited in many scientific reports. Using a newly developed patterning technique for conductive polymers, we manufactured high-resolution electrochromic devices from the complementary polymers PEDOT and polypyrrole. The technique, which combines UV-light exposure with vapor phase polymerization, has previously only been demonstrated with the conductive polymer PEDOT. We further demonstrated how the same technique can be used to control the optical properties and the electrochromic contrast in these polymers. Oxidant exposure to UV-light prior to vapor phase polymerization showed a reduction in polymer electrochromic contrast allowing high-resolution (100 μm) patterns to completely 'disappear' while applying a voltage bias due to their optical similarity in one redox state and dissimilarity in the other. This unique electrochromic property enabled us to construct devices displaying images that appear and disappear with the change in applied voltage. Finally, a modification of the electrochromic device architecture permitted a dual image electrochromic device incorporating patterned PEDOT and patterned polypyrrole on the same electrode, allowing the switching between two different images.